Manajemen Pengelolaan Keuangan pada Sekolah Menengah Kejuruan Negeri 1 Anggana - beauty kusnukiandany, Intan; Hanum Budiawati, Syifa; Herwin; Warman; Amir Masruhim, Muhammad; Nugroho, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze financial management at SMK Negeri 1 Anggana to improve the effectiveness, efficiency, and accountability of financial governance based on Good Financial Governance (GFG). The study used a descriptive qualitative approach using interviews, observations, and documentation studies, as well as analysis of the Miles and Huberman interactive model.The results indicate that school financial management adheres to the RKAS guidelines, but remains administrative in nature and is not based on real needs. Transparency and accountability are suboptimal due to limited public access and management capabilities. The implementation of the e-RKAS digital system is hampered by infrastructure and financial literacy. Key factors influencing financial effectiveness include leadership, human resource competency, and regional policy support.This study emphasizes the importance of implementing GFG in vocational education and recommends strengthening financial governance based on transparency, participation, and digitalization as a step towards financial independence in vocational schools.